Fading Roars? A Survey of the Cultural Use and Illegal Trade in Wild Felid Body Parts in Côte d’Ivoire - Robin Horion; Janvier Aglissi; Rob Pickles; Amara Ouattara; Marine Drouilly (Animals)
The illegal trade in leopard and lion parts is a major threat to felid conservation across Africa, especially in under-researched areas like francophone West Africa. Between April and June 2024, we conducted surveys in 16 cities and 46 markets in Côte d’Ivoire, interviewing 39 sellers and 14 users of felid products. We found leopard and lion parts in 42.7% and 25% of stalls, respectively. The illegal trade is driven by the demand for felid products for traditional purposes, with both species holding strong symbolic values. Products were often trafficked through informal networks and sourced from Sahelian neighboring countries like Mali and Burkina Faso. We identified some key trade routes across West Africa and beyond. Without effective control measures, this illegal trade could accelerate the decline of West Africa’s remaining large felid populations. We recommend establishing a regional database of confiscated felid parts for genetic tracing and developing standardized questionnaires for use during traffickers’ arrests to gain further insights into their operations. Additionally, targeted behavioral change campaigns should be implemented to address corruption, increase enforcement agencies’ interest and capacity, and shift the practices of traditional practitioners toward sustainable alternatives. Training law enforcement officers, raising awareness among key communities, and increasing cross-border collaboration and controls are critical to providing a more comprehensive understanding of the trade dynamics in the region.